Methane‐induced Activation Mechanism of Fused Ferric Oxide–Alumina Catalysts during Methane Decomposition. Issue 15 (27th June 2016) - Reddy Enakonda, Linga; Zhou, Lu; Saih, Youssef; Ould‐Chikh, Samy; Lopatin, Sergei; Gary, Daniel; Del‐Gallo, Pascal; Basset, Jean‐Marie
Abstract: Activation of Fe2 O3 –Al2 O3 with CH4 (instead of H2 ) is a meaningful method to achieve catalytic methane decomposition (CMD). This reaction of CMD is more economic and simple against commercial methane steam reforming (MSR) as it produces CO x ‐free H2 . In this study, for the first time, structure changes of the catalyst were screened during CH4 reduction with time on stream. The aim was to optimize the pretreatment conditions through understanding the activation mechanism. Based on results from various characterization techniques, reduction of Fe2 O3 by CH4 proceeds in three steps: Fe2 O3 →Fe3 O4 →FeO→Fe0. Once Fe0 is formed, it decomposes CH4 with formation of Fe3 C, which is the crucial initiation step in the CMD process to initiate formation of multiwall carbon nanotubes. Abstract : Change the gas : Activation of Fe2 O3 –Al2 O3 with reactant CH4 gas (instead of H2 ) is meaningful for catalytic methane decomposition (CMD) to make it more economic and simple compared to commercial methane steam reforming (MSR) to produce CO x ‐free H2 . In this study, for the first time, changes in the catalyst structural during CH4 reduction with time on stream is screened with the aim of optimizing the pretreatment conditions through understanding the activation mechanism.